'These viragoes are no less cruel than the lads'. Young women, gangs and violence in late Victorian Manchester and Salford - Davies, Andrew (The British journal of criminology, 1999)
Young women formed only a small minority of those convicted of gang-related crimes of violence in the Manchester conurbation in the last three decades of the nineteenth century. Nonetheless, press reports and court records document both their occasional participation in confrontations between rival gangs and their more frequent involvement in collective assaults upon local people and the police. Female gang members were loudly condemned as 'vixens', 'viragoes' and 'Amazons' in the local press, and were subjected to stern lectures by magistrates who deplored any evidence of 'unwomanly' behaviour. However, they generally received less stringent sentences than 'disorderly' young men. Magistrates appear to have followed local social commentators in viewing young women as marginal figures in the local gang conflicts, but also seem to have shared a broader Victorian perception of women as more malleable creatures than men